Studi Avifauna Gunung Lawu Berdasarkan Distribusi Altitudinal - Dewi Puspita Sari; Puguh Karyanto; Muzayyinah M (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
Mount lawu is the ekoton area that administratively located between Central Java and East Java Province. Research was done in qualitative exploration by using a series of the observation and identification methods. Sampling techniques used in line transect famous with the crusier method. There are four routes of climb as the location sampling: 1) Cemoro kandang (Karanganyar, Central Java), (2) Tambak (Karanganyar, Central Java), (3) Cemoro Sewu (Magetan, East Java) and (4). Jogorogo (Ngawi, East Java). Validation data was undertaken with triangulation method. Technique data were analyzed by using in descriptive qualitative. Based on the research done inferred the type of highest species found at 1900-2100 masl, while the lowest species types found at an altitude of 3100-3275 masl. Turdus poliocephalus stresmanii having spesification location foraging upon 2500-3268 masl, Apus affinis with 900-1700 masl, Cettia volcania in 3265 masl, and finnaly Falco peregrinus and Treron sphenura 3100 masl are bird with spesific distribution. Other kinds is cosmopolite by the span of distribution a relatively large amount of.Keywords: altitude distribution, avifauna, line transect, Mount Lawu